Health-related quality of life in boys with constitutional delay of growth and puberty - Kariola, Laura; Varimo, Tero; Huopio, Hanna; Tenhola, Sirpa; Voutilainen, Raimo; Kosola, Silja; Toppari, Jorma; Sintonen, Harri; Miettinen, Päivi J.; Raivio, Taneli; Hero, Matti (Frontiers in Endocrinology, 2022)
Introduction Constitutional delay of growth and puberty (CDGP) is the most common reason for delayed puberty in healthy male adolescents. The main indication for medical treatment for this condition is psychosocial burden. However, to the best of our knowledge, no previous study has addressed the impact of puberty-promoting treatment on health-related quality of life (HRQoL) among boys with CDGP. Methods We investigated HRQoL in 22 boys with CDGP, who participated in a randomized controlled trial in four Finnish pediatric endocrinology outpatient clinics between 2013 and 2017. The boys were randomized to receive either aromatase inhibitor letrozole (2.5mg/day; n=11) or intramuscular testosterone (1mg/kg/every 4 weeks; n=11) for 6 months and followed up to 12 months. HRQoL was assessed with a generic self-assessment 16D© instrument developed and validated for adolescents aged 12 to 15 years. The 16D includes 16 dimensions (vitality, sight, breathing, distress, hearing, sleeping, eating, discomfort and symptoms, speech, physical appearance, school and hobbies, mobility, friends, mental function, excretion and depression). The results were compared with an age-matched reference population that included 163 boys from the Finnish capital-city area. The study protocol is registered to ClinicalTrials.gov (registration number: NCT01797718). Results At baseline, the mean 16D score of the CDGP boys was similar to the age-matched reference population (0.95 vs 0.96, p=0.838). However, the physical appearance score (satisfaction with general appearance, height and weight) was significantly lower in the CDGP boys (0.75 vs 0.92, p=0.004) than their peers. Twelve months after treatment, Appearance had improved significantly (0.75 vs 0.87, p=0.004) and no HRQoL dimension was inferior compared to the age-matched reference population. Discussion In terms of HRQoL, the main impact of delayed puberty was dissatisfaction with physical appearance. Puberty promoting therapy was associated with a positive change in perceived appearance, with no clear difference between low-dose testosterone and letrozole treatments.